The Impact of COVID-19 Pandemic Level 3 Alert on the Incidence of Anxiety and Mood Disorder in Taiwan: An Interrupted Time Series Analysis - Pei-Yi Cheng; Chi-Chuan Wei; Li-Lin Liang; Yi-Fang Chuang (Taiwanese Journal of Psychiatry)
Objective: In this study, we intended to evaluate the impact of Taiwan’s COVID-19 pandemic Level 3 alert on anxiety and mood disorders, focusing on age and gender differences. We hypothesized that individuals aged 43+ years, who experienced the 2003 SARS epidemic during their working years, would show increased vulnerability for anxiety and mood disorder. Methods: Using Taiwan’s National Health Insurance data (2018–2021), we did an interrupted time series analysis to compare weekly mental disorder incidence before and after the COVID-19 pandemic Level 3 alert, stratified by age and gender. Results: The overall incidence did not increase, but individuals aged 43+ years were more affected: men showed a sustained, significant increase in the incidence of anxiety disorders (+0.05/100,000 person-days/week, p < 0.01), while women showed significantly more immediate responses (+1.16/100,000 person-days, p < 0.01). Conclusion: These findings highlight the lingering psychological impact of previous health crises and emphasize the need for tailored mental health interventions for high-risk groups during future pandemics or similar events.